If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = -3x + 29 Reorder the terms: 2y = 29 + -3x Solving 2y = 29 + -3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 14.5 + -1.5x Simplifying y = 14.5 + -1.5x
| -7x+9=19-3x | | -2y-3y+9=4-3-y | | 600=300+10c | | X^2-12x+49=22 | | 13y+2=9y+22 | | 97b=2037 | | 14x-9x=7 | | 11n^2=5n^2 | | 16b=128 | | 600=5s+400 | | x-.16x=543.90 | | 11x-4=117 | | x-.16=543.90 | | 600=175+10c | | 4n-3=4n-3 | | 4y^2+36y+72=0 | | 5/4(a-8=2/3 | | 3x[x-3]=6 | | 600=50+10c | | 7y-3y=18 | | x-0.24x=519.21 | | 2x-9+7x+13+41=180 | | y=-2(x+3)(x-4) | | x-.24x=519.21 | | 1.5y=3y | | x^3*y^3=216 | | ln(x+1)=ln(1.3) | | 5x+5-10(x+1)= | | 7-8p/2=28 | | 2x+8=4x-6 | | -9=6.3 | | 7-8p/2 |